Creating together – moving towards a 'we-paradigm' in educating for creativity. (2nd January 2020) - Tanggaard, Lene
ABSTRACT: Education plays a vital role in making children feel they are part of life in their society and culture. However, what is the supposed role of education in creating this sense of agency and what kinds of implications might this have for multicultural education? This paper shows how a sense of agency and social responsibility are central aspects of creativity. The paper draws on a distinction between functional and value-based education for creativity and, on this basis, it is suggested that a new, updated paradigm of creativity and innovation will teach students to think in terms of 'we' and togetherness as the central axis around which the novel idea are generated. It will teach students that creativity is often dependent on the support from others and it therefore strives for a broad and inclusive idea of education in line with recent attempts to see multicultural education as a vehicle for cultivating humanity in a global age.